Factors Influencing User Satisfaction with Information Systems: A Systematic Review: - Kalankesh, Leila R; Nasiry, Zahra; Fein, Rebecca; Damanabi, Shahla (Galen Medical Journal, 2020)
User satisfaction has been considered as the measure of information system effectiveness success. User satisfaction is difficult to define but is considered an evaluation construct. Globally health organizations, particularly hospitals, invest a huge amount of money on information system projects. If hospital information systems (HISs) are to be successful, factors influencing or related to user satisfaction should be taken into account at the time of designing, developing or adopting such systems. The current study aimed to provide a comprehensive review of factors related to user satisfaction with information systems. The researchers systematically searched PubMed, Science Direct, and IEEE electronic databases for articles published from January 1990 to June 2016. A search strategy was developed using a combination of the following keywords: â€œmodel,â€ â€œuser satisfaction,â€ â€œinformation system,â€ â€œmeasurement,â€ â€œinstrument,â€ and â€œ tool.â€ Reported dimensions, factors, and their possible influence on user satisfaction with information systems were extracted from the studies wherever was possible. Overall factors influencing user satisfaction with information systems can be categorized in seven dimensions: Information quality, system quality, vendor support quality, system use, perceived usefulness, user characteristics, and organizational structure& management style. If all these factors are considered properly in the process of developing, designing, implementing, or purchasing information systems, the higher user satisfaction with the system will be likely. Otherwise, it would end up with unsatisfied users that will finally contribute to the system failure. [GMJ.2020;9:e1686]